The speed of stock price discovery - Gavious, Arieh; Kedar-Levy, Haim (Journal of Financial Intermediation, 2013)
We develop closed-form expressions for the path and speed of stock price discovery in a utility-based CAPM with wealth effects. Two investors with uniquely bounded risk-preferences always apply opposite portfolio rebalancing trades. These trades determine the intra-period path and speed of price discovery in a Walrasian, tâtonnement setup. While conditions for maximum speed exist, convergence is rapid over a wide range of endowments and preferences. Convergence to equilibrium is exponential, and its speed depends on endowments, risk-preferences, firm size, and market price for risk. Convergence is not guaranteed, and the conditions for divergence are specified.